2022
DOI: 10.1001/jamanetworkopen.2022.39380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Intensity Interval Training in Patients With Atrial Fibrillation

Abstract: ImportancePatients with atrial fibrillation (AF) experience poor functional capacity and quality of life (QOL). High-intensity interval training (HIIT) has been shown to elicit greater improvements in functional capacity and QOL compared with moderate to vigorous intensity continuous training (MICT) in other cardiovascular populations, yet HIIT remains understudied in AF.ObjectiveTo compare the effects of 12 weeks of HIIT and MICT-based cardiovascular rehabilitation (CR) on functional capacity and general QOL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The characteristics of the included studies are summarized in Table 1 . The included studies were from 12 different countries, with Canada 25 , 29 , 39 , 47 and Norway 27 , 38 , 44 , 45 dominating the origin of articles. All articles were written in English, except for one published in China that was written in Chinese 35 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of the included studies are summarized in Table 1 . The included studies were from 12 different countries, with Canada 25 , 29 , 39 , 47 and Norway 27 , 38 , 44 , 45 dominating the origin of articles. All articles were written in English, except for one published in China that was written in Chinese 35 .…”
Section: Resultsmentioning
confidence: 99%
“…The study participants were predominantly (11/25 studies) patients with coronary heart disease. The remaining studies involved patients with HF 24 , 26 , 38 , 43 , tetralogy of Fallot 12 , heart transplantation 27 , 36 , coronary artery bypass grafting 44 , atrial fibrillation 47 , myocardial infarction 34 , stroke 37 , and hypertension 35 , 41 . Most of the studies reported the registration numbers, while eight did not 25 , 26 , 32 , 34 , 42 44 , 46 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 High-intensity interval training improves functional capacity and quality of life in AF, similar to moderate-to-vigorous continuous training. 10 …”
Section: Lifestyle Factorsmentioning
confidence: 99%